2017
DOI: 10.1021/acsnano.7b00861
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Complementary Transistors and Medium-Scale Integrated Circuits Based on Carbon Nanotube Thin Films

Abstract: Solution-derived carbon nanotube (CNT) network films with high semiconducting purity are suitable materials for the wafer-scale fabrication of field-effect transistors (FETs) and integrated circuits (ICs). However, it is challenging to realize high-performance complementary metal-oxide semiconductor (CMOS) FETs with high yield and stability on such CNT network films, and this difficulty hinders the development of CNT-film-based ICs. In this work, we developed a doping-free process for the fabrication of CMOS F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
152
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 139 publications
(163 citation statements)
references
References 39 publications
3
152
1
Order By: Relevance
“…Using randomly oriented or aligned CNT array films, various types of CNT thin-film FETs have been fabricated [9][10][11][12][13] . However, hindered by the limited performance of nanotube FETs, the operation speed of CNT integrated circuits (ICs) [20][21][22][23][24][25][26][27][28][29][30][31] typically falls short of their expected terahertz potential, and that achieved by Si CMOS circuits (gigahertz), by several orders of magnitude. Notably, CNT-based ring oscillators (ROs) with an oscillation frequency (f o ) of 282 MHz have recently been reported 32 .…”
mentioning
confidence: 99%
“…Using randomly oriented or aligned CNT array films, various types of CNT thin-film FETs have been fabricated [9][10][11][12][13] . However, hindered by the limited performance of nanotube FETs, the operation speed of CNT integrated circuits (ICs) [20][21][22][23][24][25][26][27][28][29][30][31] typically falls short of their expected terahertz potential, and that achieved by Si CMOS circuits (gigahertz), by several orders of magnitude. Notably, CNT-based ring oscillators (ROs) with an oscillation frequency (f o ) of 282 MHz have recently been reported 32 .…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] In particular, highperformance complementary metal-oxidesemiconductor (CMOS) FETs have been realized on CNT films through dopingfree technology. [10] Researchers have also demonstrated various kinds of ICs based on solution-derived CNT films, including fundamental logic and arithmetic gates, ring oscillators and even medium-scale ICs, [9][10][11] which shows the development potential of CNT film ICs in digital applications. However, the vast majority of ICs realized on CNT films are arithmetic/ logic units, and few works have addressed static random access memory (SRAM), which is an indispensable part of actual digital ICs.…”
mentioning
confidence: 99%
“…[66] High-k dielectric materials, such as HfO 2 and Al 2 O 3 , are regarded as the ideal dielectrics for constructing high-performance SWCNT transistors. Previous studies have shown that printed SWCNT TFTs have high mobility up to 20 cm 2 V −1 s −1 , and it is beneficial to associate sc-SWCNTs with highly efficient gate dielectrics to maximize their performance as channel materials.…”
Section: Resultsmentioning
confidence: 99%